2009
DOI: 10.1016/j.asr.2009.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Simulating the impact of dust cooling on the statistical properties of the intra-cluster medium

Abstract: From the first stages of star and galaxy formation, non-gravitational processes such as ram pressure stripping, SNs, galactic winds, AGNs, galaxy-galaxy mergers, etc. lead to the enrichment of the IGM in stars, metals as well as dust, via the ejection of galactic material into the IGM. We know now that these processes shape, side by side with gravitation, the formation and the evolution of structures. We present here hydrodynamic simulations of structure formation implementing the effect of the cooling by dust… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Da found a 25% normalisation change for the LX − M relation and a 10% change for the Y − M and S − M cluster scaling relations in the presence of dust. Similarly, Pointecouteau et al (2009) found changes in the LX − M relation by as much as 10% for clusters with temperatures around 1 keV for models that include dust cooling. However, those results are based on simplified dust models and it is currently unclear whether they capture the correct physical behaviour.…”
Section: Introductionmentioning
confidence: 72%
“…Da found a 25% normalisation change for the LX − M relation and a 10% change for the Y − M and S − M cluster scaling relations in the presence of dust. Similarly, Pointecouteau et al (2009) found changes in the LX − M relation by as much as 10% for clusters with temperatures around 1 keV for models that include dust cooling. However, those results are based on simplified dust models and it is currently unclear whether they capture the correct physical behaviour.…”
Section: Introductionmentioning
confidence: 72%
“…At scales of hundreds of kiloparsec hot gas (10 6 − 10 7 K) needs to cool in order to accrete into galaxies to fuel their on-going star-formation. The classical explanation for the cooling of gas is through bremstrahlung or line emission in the Xray, although inelastic collisions with dust grains is the most efficient mechanism for gas cooling at these temperatures (Dwek & Werner 1981;Popescu et al 2000a;Montier & Giard 2004;Pointecouteau et al 2009;Natale et al 2010;Vogelsberger et al 2018), providing grains exist in the IGM around star-forming galaxies. At kiloparsec scales within the disc of galaxies dust grains heat the ISM via the photoelectric effect and the thermodynamic balance of the gas is maintained through an equality between the photoelectric heating and the FIR cooling lines powered by inellastic collisions with gas particles (e.g.…”
Section: ;mentioning
confidence: 99%
“…Thus, the ICD in Virgo acts as a gas coolant and contributes to a change in the statistical properties of the Virgo ICM (e.g. Montier & Giard 2004;Pointecouteau et al 2009;Vogelsberger et al 2019).…”
Section: Physical Properties Of the Virgo Dustmentioning
confidence: 99%